Akselerasi Pemahaman Mahasiswa Perbankan Syariah melalui Pembelajaran Media Online di STAIN Mandailing Natal - Riska Siregar; Siti Kholijah; Azizatur Rahmah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to measure the accelerated level of understanding of Islamic Banking students at STAIN Mandailing Natal regarding Islamic banking systems and products through online media. The method used is a quantitative descriptive approach with primary data analysis. The research results show that students' understanding has increased significantly, as measured through pre-test and post-test. The average pre-test score was 56.47, while the post-test reached 62.82. The post-test t-value of 4.462 exceeds the t-table of 1.740 with a significance value of 0.000, which shows the results are significant at the 5% level. These findings indicate that learning through online media is effective in increasing students' understanding of sharia banking systems and products. It is hoped that this research can contribute to the development of learning methods in the field of sharia banking.